Impact of Twitter communication on the environmental movement during COP15 - Rodríguez Hernández, Jonattan (2024)
The research analyzes the Twitter network made up of users and their interactions during the Conference of the Parties (COP) COP15 held in Montreal from December 7 to 19, 2022. The main objective is to measure the characteristics of the network and identify the key players in the conversation and the main topics addressed. We also sought to recognize if there was any relationship between the format of the messages and the level of engagement. To carry out the analysis, we used a methodology that combined quantitative and qualitative social network analysis techniques. The results suggest that communication through Twitter was a key factor in the successful mobilization of the environmental movement during COP15 and in raising awareness of the need to take concrete actions to address climate change. Likewise, the highest engagement was generated by mostly critical and urgent messages, focused on the need to take concrete action to address the biodiversity and climate change crisis. This reflects a separation between the activism reflected in the network and the scientific and political leadership present at the Summit.